POWER AND LIMITS OF HUMAN CONSCIOUSNESS - Shakarov Bobur Khusniddinovich; Shokirjonova Shahzoda Zohid kizi; Sharipova Dinora Salohiddin kizi (Western European Studies, 2025)
This article provides an extensive examination of the structure and functional mechanisms of human consciousness, focusing on its evolutionary origins and the formation of cognitive processes. The power of consciousness is analyzed through its flexibility in perception, advanced abstract thinking, symbolic reasoning, and higher-order mental operations. Furthermore, the article scientifically discusses the biological limits of the mind, including attention selectivity, memory capacity, and sensory constraints. Integrating perspectives from neuropsychology, cognitive science, philosophy, and educational theory, the study offers a comprehensive view of both the capabilities and inherent limitations of human consciousness.
Keywords: consciousness; human brain; cognitive processes